2019
DOI: 10.1111/cod.13344
|View full text |Cite
|
Sign up to set email alerts
|

Contact allergy to fragrances and formaldehyde contributing to papulopustular rosacea

Abstract: Allergic contact dermatitis caused by fragrances and formaldehyde is common, 1,2 but pustular dermatitis as a manifestation of contact allergy is rare. 3 We report a case of therapy-resistant rosacea for which (occupational) contact allergy to fragrances, and to a lesser extent formaldehyde, was identified as an aggravating factor. CASE REPORTA 50-year-old non-atopic female hairdresser began to suffer from erythematous and pustular dermatitis on the cheeks, forehead, and chin ( Figure 1). Having been diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…2 The most common adverse cutaneous effects of azelaic acid are burning/stinging/tingling and pruritis. 1 A literature search found two cases of allergic contact dermatitis mimicking rosacea due to fragrance and/or formaldehyde allergy, 3,4 and one case of allergic contact dermatitis to an azelaic acid-containing gel, but not to azelaic acid itself. 5 Here, inactive ingredients were negative; thus, azelaic acid was suspected to be the allergen.…”
Section: Discussionmentioning
confidence: 99%
“…2 The most common adverse cutaneous effects of azelaic acid are burning/stinging/tingling and pruritis. 1 A literature search found two cases of allergic contact dermatitis mimicking rosacea due to fragrance and/or formaldehyde allergy, 3,4 and one case of allergic contact dermatitis to an azelaic acid-containing gel, but not to azelaic acid itself. 5 Here, inactive ingredients were negative; thus, azelaic acid was suspected to be the allergen.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, impetigo and rosacea(‐like dermatitis) have been highlighted. The latter has been reported as a predominant clinical feature of FA contact allergy, 50‐51 and some studies have shown that it is a primary culprit allergen in patients with rosacea and co‐existent facial ACD 52 . The skin irritation potential of FA, and FRs such as imidazolidinyl urea and particularly DMDM hydantoin may also provoke mild (facial) erythema 53 …”
Section: Clinical Picturementioning
confidence: 99%
“…Formaldehyde is found naturally in small amounts in many foods, especially apples, grapes, plums, and bananas, and vegetables (cauliflower, spinach, onions, and shiitake mushrooms), meat (pork, smoked ham, beef, and poultry), seafood, coffee, and tofu. Formaldehyde can stimulate the TRPA1 receptor as well as directly irritate nociceptors in sensory neurons, causing rosacealike changes [31]. Popular histamine-rich foods include fruit (avocados, bananas, papaya, and pineapples), dried fruit (apricots, dates, raisins, and figs), vegetables (tomatoes, spinach, and eggplants), nuts (cashews, walnuts, and peanuts), milk cow, fermented products and smoked fish.…”
Section: Promieniowanie Słonecznementioning
confidence: 99%
“…Formaldehyd występuje naturalnie w niewielkich ilościach w wielu produktach spożywczych, zwłaszcza w jabłkach, winogronach, śliwkach i bananach oraz warzywach (kalafior, szpinak, cebula i grzyby shiitake), mięsie (wieprzowina, wędzona szynka, wołowina i drób), owocach morza, kawie i tofu. Formaldehyd może pobudzać receptor TRPA1, jak również bezpośrednio podrażniać nocyceptory w neuronach czuciowych, co powoduje zmiany w postaci trądziku różowatego [31]. Popularne pokarmy bogate w histaminę to owoce (awokado, banany, papaja i ananasy), suszone owoce (morele, daktyle, rodzynki i figi), warzywa (pomidory, szpinak i bakłażany), orzechy Dermatology Review/Przegląd Dermatologiczny 2022/2 increases angiogenesis.…”
Section: Dietaunclassified